AN OVERVIEW OF ACCULTURATION STRATEGIES APPLIED BY THE INDONESIAN STUDENTS LIVING IN TAIWAN - Risaharti, Risaharti; Chilin Wang, Chilin Wang (JURNAL SERAMBI ILMU, 2018)
This article provides an overview of acculturation strategies applied by the Indonesian students living in Taiwan. The sample was drawn from twenty-six Indonesian students living from northern part to southern part of Taiwan. Data were collected with multiple methods: open question survey, follow-up interviews, emails, and their Facebook (FB) communication. Among the four acculturation strategies proposed by Berry (2005): assimilation, integration, marginalization, and separation, the results from participants’ responses indicated that integration is applied better than other strategies. Separation is the second favored mode used by most Indonesian students to acculturate, while assimilation and marginalization are the least preferred by the Indonesian students. After acculturation efforts they made, it bolds them clearer perception of their cultural identity.